A principled engagement?: non-collaboration and the Teachers' League of South Africa in the Western Cape, 1990-2003 - Hendricks, Paul Ross (School of Education, 2017)
This thesis investigates the Teachers' League of South Africa's (TLSA, League or Teachers' League) ideas and practice of non-collaboration. It seeks to ascertain whether these ideas and practices continued after the organisation merged with several public sector unions in the National Union of Public Service and Allied Workers (NUPSAW) at the end of the last century. The thesis tracks the emergence and changing dynamics of the TLSA from the early decades of the twentieth century, as it developed and grew in the Western Cape, a region that was its nerve centre and where it was most active. There is a focus on the endeavours of the League to adapt and grow during the political and educational tumult of the 1990s, a period characterised by negotiations, reconciliatory and consensual politics that centred on nation building, and which was unreceptive if not clearly hostile to the organisation's non-collaborationist stance. The thesis employs an historical approach to contextualise the development of the League's non-collaborationism, and to elucidate the impact of South Africa's changing political, economic and educational landscape on the organisation. Extensive interviews were conducted, therewith giving a voice to the writing of history from below, embracing the experiences and perceptions of League members and the teacher activists who interacted with them before, but more so during and even beyond the 1990s. Documentary material of the TLSA and its umbrella body, the Unity Movement, dating back to the 1940s, provides the key primary sources for the study, while secondary information on the development of South Africa's political economy and the liberation movement offers valuable insights and alternative perspectives on the TLSA and Unity Movement. The thesis endorses the notion that appearances are at times intermingled with the opposite of what is being perceived, and thus challenges assumptions that the League's policy of non-collaboration was fixed and timeless. Instead, the thesis seeks to uncover the incongruities, nuances and complexity of this distinctive quality of the organisation, in an attempt finally, to elucidate its transformative potential in the present period.